Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41598-023-32477-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on tilting deformation and a new method for landslide prediction with retaining-wall locked segment

Abstract: The destruction of the locked-segment type landslide is often accompanied by the destruction of the locked segment with cumulative effects. Investigating the failure mode and instability mechanism of locked-segment type landslides is crucial. The study uses physical models to examine the evolution of locked-segment type landslides with retaining-walls. It utilizes a variety of instruments (tilt sensors, micro earth pressure sensors, pore water pressure sensors, strain gauges, and others) to conduct physical mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Deformation is the most important external manifestation of slope failure, and the type and characteristics of slope deformation over time are the most effective means for early landslide warnings [42,43,47,48]. For the slope without any mitigation measures (Figure 5), after 6 min of rainfall, the water began to flow on the slope surface, and then the surface began to be eroded.…”
Section: Deformationmentioning
confidence: 99%
“…Deformation is the most important external manifestation of slope failure, and the type and characteristics of slope deformation over time are the most effective means for early landslide warnings [42,43,47,48]. For the slope without any mitigation measures (Figure 5), after 6 min of rainfall, the water began to flow on the slope surface, and then the surface began to be eroded.…”
Section: Deformationmentioning
confidence: 99%
“…That is a milestone and successfully applied in multiple landslides, especially loess landslides (Xu et al, 2020). Liu et al (2023) suggested a tilting angle that is 0.34°, 1.89°, and 4.38°, respectively, when the modeled landslide enters the initial, medium, and fast creeping stages. However, fixed thresholds may not be applicable to all the landslides.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most dominant approaches is to predict landslides by comprehending the physical mechanisms of landslide formation using physical equations and numerical simulation methods. Liu et al [2] utilize physical modeling and various instruments to study the evolution and instability of a locked segment landslide under rainfall conditions and identify tilting deformation as a standard for landslide instability. Capparelli et al [3] use a physical model, SUSHI, to simulate the role of subsurface hydrology in rain-induced landslides in Campania, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…This paper has the following main contributions: (1) We propose a workflow for landslide susceptibility evaluation combining spatio-temporal knowledge graphs and machine learning model. (2) We propose a method for organizing remote sensing environmental data based on semantic structure, and improve the efficiency of remote sensing data usage by constructing schema. (3) We define inference rules for candidate model selection and environmental similarity analyses to reduce the impact of sample scarcity on landslide prediction results.…”
Section: Introductionmentioning
confidence: 99%